DUI MENRE DALAM TRADISI PERKAWINAN BUGIS DALAM PERSPEKTIF HUKUM ISLAM - Sesse, Muh. Sudirman; Rafsanjani, Rafsanjani (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2011)
This study describes the problem Dui Menre in Bugis Marriage Traditions in the perspective of Islamic law. The type of research is to study the phenomenology. While the data analysis techniques used were: 1) Analysis of Inductive, 2) a deductive analysis, and 3) Comparative Analysis. From the research results obtained information and the understanding that: 1) Dui Menre in the tradition of marriage in the District Bugis Bacukiki Parepare City is one of the mandatory requirement in customary marriage Bugis. 2) The response of the Bugis community Menre Dui, Dui Menre that the number of marriages in Bugis tradition is high and becomes a burden for the men to hold the marriage. 3) Law Dui Bugis Menre in the tradition of marriage is permissible under Islamic law to be done and does not constitute one of the pillars and conditions of the implementation of a marriage.